Analyzing the impact of microstructural defects on the failure response of ceramic fiber reinforced aluminum composites. (15th October 2016) - Ahmadian, Hossein; Liang, Bowen; Soghrati, Soheil
Abstract: The computational homogenization technique is employed to investigate the effect of pre-existing microstructural voids on the failure response of a ceramic fiber reinforced aluminum composite subjected to loads in transverse to the fiber direction. Automated numerical simulations are carried out using a hierarchical interface-enriched finite element method (HIFEM), which enables the use of simple structured meshes for creating the discretized model. The HIFEM is integrated with a new microstructure quantification algorithm relying on the Random Sequential Adsorption (RSA) and Non-Uniform Rational B-Splines (NURBS) to create realistic periodic unit cells of the composite based on imaging data. A strain-driven homogenization problem is then solved at the microscale to simulate the damage evolution in the aluminum matrix using the Lemaitre elasto-plastic damage model. Six virtual models of the composite microstructure with varying volume fractions and spatial distributions of pre-existing voids are analyzed to determine their failure responses subject to macroscopic normal and shear strains. The outcomes of this study indicate that although for the latter type of loading the impact of small volume fractions of voids on the failure response is negligible, their presence significantly deteriorates the composite mechanical strength subject to uniaxial and equi-biaxial macroscopic normal strains.